The Need Analysis for AI-Based Applications to Support Teacher Performance - Raihan Primasta Putra; Pujiriyanto Pujiriyanto (Journal of Innovation in Educational and Cultural Research, 2025)
In the digital transformation era, teachers play a pivotal role in shaping educational outcomes while facing challenges posed by modern curricula, including Indonesia's Merdeka Curriculum. This study investigates teachers' specific needs for AI-based applications, focusing on lesson planning, administrative tasks, and personalized teaching approaches. Employing a cross-sectional survey, data were collected from 300 teachers across Java and Bali, spanning early childhood to vocational education. The findings highlight significant difficulties in aligning lessons with student-centered principles and diverse learner needs despite considerable enthusiasm for AI's potential to reduce workloads and enhance efficiency. Nonetheless, ethical concerns and limited training remain issues. Critical factors for successful AI adoption include time efficiency, ease of use, curriculum alignment, and cost. These insights guide developers and policymakers in creating localized, user-friendly, and accessible AI solutions. In conclusion, effectively designed AI-based tools, coupled with sufficient professional development, can improve teacher readiness and performance, offering a pathway to more effective implementation of the Merdeka Curriculum and advancing Indonesia's educational landscape.